Public geographies through social media. (March 2013) - Kitchin, Rob; Linehan, Denis; O'Callaghan, Cian; Lawton, Philip
In this paper, we argue that new social media produces new forms of public geography and digital praxis in which the relationship between reader and writer is radically altered and which enables geographers to engage in timely conversation and debate with the public on unfolding issues, and provides new avenues to connect with older forms of broadcast media. Social media can strengthen geographers engagement with the existing fourth estate and forge new relationships with an emerging fifth estate – dynamic, responsive and empowered publics. We illustrate such potentials by drawing on our own experiences of contributing to IrelandAfterNAMA, a collective blog that provides critical analysis of the present crisis in Ireland which has established a regular readership and has led to significant media work (over 500 newspaper articles and radio and television interviews). Such public geography projects are not without their challenges and pitfalls, not least because they alter and challenge the ways in which academics work, communicate and are assessed. Nevertheless, we believe that at the very least their quotidian practices enact what Macgilchrist and Bőhmig (2012: 97) term 'minimal politics', creating 'tiny fissures in the mediascape' that inform and engage with wider publics in ways that academic articles rarely do and work to challenge hegemonic formations.